Fingerprint Matching Using Pores Extracted with Machine Learning - Rocha, Ciro Moraes; Vasconcelos, Raimundo Claudio da Silva (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2025: Anais Estendidos da XXXVIII Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2025.38317, 2025)
Fingerprint recognition is widely used for biometric applications due to its uniqueness and convenience. However, traditional systems often overlook level 3 features, particularly pores, which can improve precision, especially in partial or latent fingerprints. The integration of these features is highly beneficial in contexts such as forensic analysis, where complete fingerprint patterns are not always available. This work proposes a pore detection model, which is a convolution neural network with U-Net architecture followed by a pore matching algorithm, applied to the dataset L3-SF, a collection of extremely realistic, labeled synthetic fingerprints. The results demonstrated high effectiveness, achieving high accuracy in pore detection and matching even in partial fingerprint images, outperforming many existing methods and, consequently, the power of deep learning applied to biometrics.